Optimalisasi Pengelolaan Perpustakaan sebagai Pusat Literasi dan Informasi Keislaman: Studi di Perpustakaan MUI Sumatera Utara - Rizky Ramadhani Batubara; Imelda Fedian; Elpi Dayanti Siregar; Mahathir Muhammad Hutasuhut; Masliani Masliani; Dwi Wulandari; Shalihah Shalihah (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to analyze strategies for optimizing the management of the library of the Majelis Ulama Indonesia (MUI) of Sumatera Utara Province in carrying out its role as an authoritative center for Islamic literacy and information. As an institution overseeing the Pendidikan Tinggi Kader Ulama (PTKU), the library holds a strategic position but faces challenges in terms of standardization and digital adaptation. The method employed is a descriptive qualitative study examining aspects of collection management, compliance with the National Library Standards (SNP), and the implementation of information technology. The findings indicate that the MUI North Sumatra Library possesses notable strengths in its collection of centuries-old classical kitab kuning manuscripts and unique documents from scholars’ deliberative forums (muzakarah). Optimization efforts include manuscript digitization using the Senayan Library Management System (SLiMS), management training for PTKU students, and the integration of information services through the organization’s official portal. The study concludes that strengthening human resource capacity, ensuring sustainable budget support, and meeting physical facility standards are key factors in transforming the library into an intellectual beacon of Islam in the Media 4.0 era.